Non-genetic risk factors in haemophilia A inhibitor management - the danger theory and the use of animal models - Lövgren, K. M.; Søndergaard, H.; Skov, S.; Wiinberg, B. (Haemophilia : the official journal of the World Federation of Hemophilia, 2016)
In haemophilia A (HA) management, antidrug antibodies, or inhibitors, are a serious complication that renders factor VIII (FVIII) replacement therapy ineffective, increases morbidity and reduces quality of life for affected patients. Inhibitor development aetiology is multifactorial and covers both genetic and therapy related risk factors. Many therapy‐related risk factors have proven difficult to confirm due to several confounding factors and the small study populations available. However, clinical studies indicate that e.g. on‐demand treatment and surgery affect inhibitor development, and explanations for this association are being investigated. A potential explanation is the danger signal effect, where the immune response is activated by endogenous or exogenous danger or damage signals present at the time and site of FVIII administration. The danger theory explains how alarm signals from stressed, injured or dying cells can activate an immune reaction, without the involvement of foreign antigens. Bleeds, trauma, surgery or concomitant infection could be events initiating danger signalling in HA patients, resulting in an immune reaction towards administered FVIII that otherwise would pass unnoticed. This role of danger in HA inhibitor formation has previously been suggested, but a thorough discussion of this subject is lacking. The present review will discuss the potential role of danger signals in haemophilia and inhibitor development, with focus on treatment related risk factors with a suspected danger signal aetiology; on‐demand treatment, treatment during major bleeds or surgery, and treatment during infection or vaccination. Clinical studies as well as animal experiments addressing these factors will be reviewed.